Primary sarcoidosis of the breast, a case study in connection with Propionibacterium acnes infection - Yoshifumi Matsushita; Keisuke Uchida; Emi Takazaki; Nobuaki Hirose; Yoshinobu Eishi (Elsevier, 2017)
A 77-year-old female underwent screening mammography with abnormal results. Core needle biopsy revealed a granulomatous lesion without necrosis, and sarcoidosis was considered although tuberculosis and granulomatous mastitis could not be ruled out. Three months later, the patient detected breast and axillary masses. Malignancy was suspected and both lesions were excised. The specimens contained epithelioid cell granulomas with no necrosis. Her angiotensin-converting enzyme level was normal, and radiographic examination revealed no evidence of involvement of other organs, including the lungs and mediastinal lymph nodes. Although sarcoidosis was highly suspected, it was not definitive. Immunohistochemistry with the PAB antibody, which specifically reacts with Propionibacterium acnes, the most commonly implicated causative agent of sarcoidosis, showed positive signals in granulomatous inflammation of the breast and within granulomas of the sentinel lymph node. This is the first case report of primary sarcoidosis of the breast involving the draining lymph node with confirmed P. acnes infection. Keywords: Immunohistochemistry, Mammary sarcoidosis, Isolated sarcoidosis, PAB antibody, Granulomatous mastitis, Tuberculosis mastitis